Assessing how biofilms modulate stream periphyton metacommunity assemblage: A translocation experiment - Daniel Zamorano; Travis Ingram; Fabio A. Labra; Christoph D. Matthaei (Ecology, 2025)
The role of three‐dimensional structural complexity in shaping communities has been increasingly studied, and evidence indicates that vertical stratification favors coexistence through niche partitioning. Despite the clear relationship between three‐dimensional structure and community assemblages, its role in shaping metacommunity processes is still unclear. To address this knowledge gap, we carried out a translocation experiment using stream periphyton (benthic microalgae) as a model community. Structural complexity in stream periphyton is observed when thicker biofilms develop, reducing hydraulic stress and improving nutrient uptake, particularly for understory taxa. In this experiment, we exposed ceramic tiles in a source river for 4, 11, or 21 days, creating a biofilm biomass and successional gradient. We then translocated these tiles to 10 receiving rivers in two phosphorus enrichment categories (low, high). After 25 days, we collected all tiles and evaluated biofilm biomass and the periphyton community. We determined community similarity post‐translocation using the Bray–Curtis distance, comparing translocated tiles to pre‐translocation communities and to control tiles from the receiving rivers. Translocated tiles remained more similar to their pre‐translocation community when the source and receiving rivers were more similar to each other and when pre‐colonization time was longer (11 or 21 days), whereas biofilm biomass was not a key predictor. Further, translocated tiles became more similar to their receiving river communities when pre‐colonization time was shorter (4 days) and when receiving river biofilm biomass was higher, suggesting that neighborhood biofilm biomass could indicate local propagule pressure. Low‐phosphorus sites exhibited lower biofilm biomass and high proportions of taxa from both receiving rivers and the source river on translocated tiles, which indicated a more important role of species sorting. By contrast, high‐phosphorus sites displayed greater neighborhood biomass and translocated tiles less similar to receiving rivers or the source river due to a higher proportion of rare taxa, which suggested mass effects. This experiment expands our knowledge of the role of three‐dimensional community structure in driving metacommunity processes by considering environmental contexts, biomass as a proxy of structural complexity, and successional time.